Pasca-Apokaliptik: Hubungan Alam dan Manusia pada Anime Gin’iro No Kami No Agito Karya Keiichi Sugiyama - Jelia, Ni Made Dwi Marta; Wiriani, Ni Made; Oeinada, I Gede (Pustaka : Jurnal Ilmu-Ilmu Budaya, 2024)
The title of this research is "Post-Apocalyptic: The Relationship Between Nature and Humanity in the Anime 'Gin'iro No Kami No Agito' by Keiichi Sugiyama." The purpose of this study is to describe the portrayal of post-apocalyptic life, environmental values, and the relationship between nature and humanity in the anime 'Gin'iro No Kami No Agito.' The research methodology in this study is the qualitative descriptive method. For the theoretical framework, the study draws from the field of literary ecocriticism, as formulated by Glotfelty. Based on the research findings and analysis conducted, the relationship between nature and humanity in the anime 'Gin'iro no Kami no Agito' leans toward a more positive orientation in the post-apocalyptic era. In this context, humanity places a strong emphasis on fostering harmony with nature, which is reflected in their behavior that consistently takes into account the well-being of the environment. However, the repercussions of the apocalyptic event also give rise to negative interactions, such as the anxiety experienced by humans due to the pressure exerted by the forest and the actions of Laguna City, which employ force to subdue nature. Consequently, the anime depicts how humans, in general, experience a sense of being burdened by the natural world, leading to anxiety and resistance. This results in an unstable relationship between humanity and nature, ultimately dividing the human population into two groups: Neutral City and Laguna City.